Deposition of thin films using argon/acetylene atmospheric pressure plasma jet - Ricci Castro, Alonso H. [UNESP]; Kodaira, Felipe V.P. [UNESP]; Prysiazhnyi, Vadym [UNESP]; Mota, Rogerio P. [UNESP]; Kostov, Konstantin G. [UNESP] (Elsevier, 2017)
Atmospheric pressure plasma jet was used to deposit polymer films from argon/air/acetylene mixture. Depending on the gas composition, three modes of operation were observed and characterized. The film deposited by a stationary jet had a circular shape with area (where thickness was almost constant) about the nozzle inner diameter. The deposition rate of stationary jet decreased with the time: a film of 2 μm was obtained after the first two minutes, while in the next two minutes only 1.3 μm film was deposited. The plasma polymers were characterized by infrared spectroscopy, where variety of C–H and few C–O bonds were detected. By using a linear displacement system, we obtained homogeneous deposition over a larger area with deposition rate of about 330 nm/min, showing the potential of such plasma jet system for large-scale depositions.
Keywords: Acetylene; Atmospheric pressure plasma; Plasma jet; Plasma polymers